А PROBLEM OF ACUTE KIDNEY INJURY IN CHILDREN TODAY - Lavrenchuk, O. (Ukrainian Journal of Nephrology and Dialysis, 2017)
In this survey of contemporary foreign literature presents the results of recent studies on acute kidney damage in children. Present modern system of stratification by severity degrees ofacute kidney injury and their comparison (RIFLE and AKIN – criteria). For this reason recently there has been a great surge of interest in identifying biomarkers ofacute and chronic kidney injury which help to detect early pathological changes in kidneys, to differentiate the injury of different parts of the nephron, to accurately determine the stage of the process, to assess the severity of inflammation and fibrogenesis intensity. The most important new markers which are currently studied include KIM–1, VEGF–А, L–FABP, TGF–b1, NGAL and NAG. This review highlights the results of major recent studies in this area.